2018
DOI: 10.4049/jimmunol.1800162
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 Enables Antibody Responses to Bacterial Polysaccharides by Promoting B Cell Receptor Diversity

Abstract: Polysaccharide vaccines such as the Vi polysaccharide (ViPS) of serovar Typhi induce efficient Ab responses in adults but not in young children. The reasons for this difference are not understood. IL-7 dependency in B cell development increases progressively with age. IL-7Rα-mediated signals are required for the expression of many V gene segments that are distal to D-J in the IgH locus and for the complete diversification of the BCR repertoire. Therefore, we hypothesized that B cells generated in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 70 publications
(102 reference statements)
1
18
0
Order By: Relevance
“…We have previously shown that murine antibody responses to Pneumovax23 require IL-7 (3). Recently, we have found that IL-7-deficient mice are also impaired in responding to ViPS (41). Since the data from the present study obtained using these two bacterial PS vaccines show that TdT is dispensable for the generation of protective antibody responses, it is likely that IL-7 plays a role in generating antibody responses to some PS antigens independently of TdT.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…We have previously shown that murine antibody responses to Pneumovax23 require IL-7 (3). Recently, we have found that IL-7-deficient mice are also impaired in responding to ViPS (41). Since the data from the present study obtained using these two bacterial PS vaccines show that TdT is dispensable for the generation of protective antibody responses, it is likely that IL-7 plays a role in generating antibody responses to some PS antigens independently of TdT.…”
Section: Resultsmentioning
confidence: 49%
“…It was previously shown that the majority of adult human B cells that bind to PPS serotypes 14 and 4 utilize distal V H genes V H 3-74 and V H 3-48 (44), whereas those that bind to PPS serotypes 6b and 23f utilize the V H 3-23 located in the center of the human Ig heavy-chain locus (45,46). We have recently found that the majority of ViPS-binding B cells of adult wild-type mice express immunoglobulin heavy-chain sequences containing distal V H gene segments, the most frequent of which were V H 1-53 and V H 1-55 (41). Therefore, the reasons for the impaired anti-PS responses in the young could be attributable to a restricted Ig repertoire due to an inefficient expression of distal V H genes.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike adults, young children and infants do not respond to polysaccharide antigens such as ViPS. We have previously shown that 3-week-old mice (like young children) do not respond to ViPS e ciently due to a restricted antibody repertoire 42 . Therefore, we compared antibody responses to ViPS in young (3week-old) and adult (8-12-week-old) CC003/Unc mice.…”
Section: Resultsmentioning
confidence: 99%
“…This strain of S. Typhimurium, referred to as RC60, was shown to exhibit cell surface and other characteristics of S. Typhi 4 . Using the S. Typhimurium strain RC60, we were able to identify several aspects of the anti-ViPS antibody repertoire required for protective immunity in vivo 35,42,51 . Thus, the use of S. Typhimurium as a "surrogate" model to understand certain virulence mechanisms of S. Typhi has been justi ed.…”
Section: Discussionmentioning
confidence: 99%
“…This strain of S. Typhimurium, referred to as RC60, was shown to exhibit cell surface and other characteristics of S. Typhi 4 . Using the S. Typhimurium strain RC60, we were able to identify several aspects of the anti-ViPS antibody repertoire required for protective immunity in vivo 34,43,52 . Thus, the use of S. Typhimurium as a "surrogate" model to understand certain virulence mechanisms of S. Typhi has been justified.…”
Section: Discussionmentioning
confidence: 99%